Assessment of Physicochemical Parameters of Drinking Water in the Schools of Bagnashkali, Palpa, Nepal - Khadka, Devendra; Khanal, Greeshma (Tribhuvan Journal, 2023)
This study aims to assess the physicochemical parameters of drinking water in schools in the Bagnashkali Rural Municipality in Nepal according to standard methods. Physicochemical analysis was performed at the Department of Chemistry at Tribhuvan Multiple Campus, Palpa, in March 2022 using samples collected randomly from different schools. The study found that water samples from schools in Bagnashkali meet NDWQS and WHO guidelines as pH (7.28- 7.98), hardness(60-140 mg/L), conductivity (65.3-173.2 µs/cm), alkalinity (46-96.6 mg/L), chloride (0.3-0.7 mg/L), dissolved oxygen (9.12-12.6 mg/L), total dissolved solids (9.12-12.6 mg/L), free CO2 (7.04-10.56 mg/L) and iron (0.017-0.068 mg/L) which were all except for temperature within acceptable limits. The temperature of the water samples in this study ranged from 21°C to 28°C. The study found that the water quality in the selected schools was good and met the acceptable standards in terms of physicochemical parameters.